The Dual Role of KIP-Kuliah in Enabling and Constraining Low-Income Students Thriving in Indonesian Higher Education - Yamin Liu; Elva Retnawati (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2026)
In Indonesia, the Kartu Indonesia Pintar Kuliah (KIP-Kuliah) scholarship program is a vital investment to support low-income students in higher education. While crucial for access, there remains limited understanding of how this aid affects students’ holistic development beyond mere enrollment or persistence. This study investigates how KIP-Kuliah influences key dimensions of student thriving (academic engagement, psychological well-being, and social connectedness) while also identifying implementation barriers that may hinder its full potential. An explanatory sequential mixed-methods design was employed. Quantitative data from 386 scholarship recipients were analyzed using Structural Equation Modeling (SEM), complemented by qualitative insights from essay-style narratives with 79 participants, analyzed through reflexive thematic analysis. KIP-Kuliah significantly predicted greater academic engagement (β=.45), psychological well-being (β=.38), and social connectedness (β=.40). The reduction of financial stress partially mediated these relationships, explaining 44–58% of the total effects. However, implementation challenges, including disbursement delays (affecting 40% of recipients), insufficient stipends (22%), and perceived stigma (28%) significantly weakened these benefits. Qualitative themes highlighted underlying mechanisms such as cognitive liberation, social capital accumulation, and enhanced psychological security. KIP-Kuliah serves as a powerful enabling mechanism that can unlock low-income students’ capacity for holistic success. However, its effectiveness is highly dependent on the quality of implementation. To maximize impact, policymakers and institutions must ensure timely disbursement, provide adequate living support, and foster inclusive campus environments that actively reduce stigma.